2022
DOI: 10.3389/fpsyg.2022.944670
|View full text |Cite
|
Sign up to set email alerts
|

Synchronizing with the rhythm: Infant neural entrainment to complex musical and speech stimuli

Abstract: Neural entrainment is defined as the process whereby brain activity, and more specifically neuronal oscillations measured by EEG, synchronize with exogenous stimulus rhythms. Despite the importance that neural oscillations have assumed in recent years in the field of auditory neuroscience and speech perception, in human infants the oscillatory brain rhythms and their synchronization with complex auditory exogenous rhythms are still relatively unexplored. In the present study, we investigate infant neural entra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 58 publications
1
4
0
Order By: Relevance
“…Neural tracking was observed in both speech that was fully audiovisual (AV-condition), in which the speaker's face was fully visible, and in the audiovisual-blocked (AV-Blocked) condition, where the speaker's visual speech cues were occluded with a block. These results are consistent with other recent findings demonstrating infants' neural tracking of auditoryonly and audiovisual speech (Attaheri, Ní Choisdealbha, Di Liberto, et al, 2022;Cantiani et al, 2022;Çetinçelik et al, 2023;Jessen et al, 2019;Kalashnikova et al, 2018;Menn, Michel, et al, 2022;Menn, Ward, et al, 2022;Ortiz Barajas et al, 2021;Power et al, 2012;Tan et al, 2022).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Neural tracking was observed in both speech that was fully audiovisual (AV-condition), in which the speaker's face was fully visible, and in the audiovisual-blocked (AV-Blocked) condition, where the speaker's visual speech cues were occluded with a block. These results are consistent with other recent findings demonstrating infants' neural tracking of auditoryonly and audiovisual speech (Attaheri, Ní Choisdealbha, Di Liberto, et al, 2022;Cantiani et al, 2022;Çetinçelik et al, 2023;Jessen et al, 2019;Kalashnikova et al, 2018;Menn, Michel, et al, 2022;Menn, Ward, et al, 2022;Ortiz Barajas et al, 2021;Power et al, 2012;Tan et al, 2022).…”
Section: Discussionsupporting
confidence: 93%
“…Successful neural tracking of the speech envelope has been repeatedly demonstrated in infants and young children (Attaheri, Ní Choisdealbha, Di Liberto, et al, 2022;Cantiani et al, 2022;Çetinçelik et al, 2023;Jessen et al, 2019;Kalashnikova et al, 2018;Menn, Michel, et al, 2022;Menn, Ward, et al, 2022;Ortiz Barajas et al, 2021;Power et al, 2012;Tan et al, 2022), and infants' neural speech tracking at the stress and syllable rate has been linked to their later vocabulary outcomes (Attaheri, Ní Choisdealbha, Di Liberto, et al, 2022;Çetinçelik et al, 2023;Menn, Ward, et al, 2022;. Yet, only a few studies have investigated whether infants' and children's neural tracking is enhanced in the presence of audiovisual speech cues.…”
Section: Introductionmentioning
confidence: 99%
“…Developmentally, it has been suggested that the perception of timing and rhythm are the primary building blocks for complex auditory perception (Trainor & Marsh-Rollo, 2019), with dramatic abilities to process and discriminate auditory rhythms evident within the first few months of life (Baruch & Drake, 1997;Lewkowicz, 2003;Winkler et al, 2009). And in keeping with the mechanism of auditorymotor entrainment just described, rhythmic patterns entrain neural activity in infants as young as 7 months, as demonstrated by EEG responses being frequency-locked to rhythmic patterns (Cantiani et al, 2022;Cirelli et al, 2016).…”
mentioning
confidence: 87%
“…Rhythmic entrainment occurs in individuals with little to no musical training and has also been shown to persist in the presence of acquired movement disorder including Parkinson’s disease ( Thaut et al, 2001 ; Nombela et al, 2013 ) and stroke ( Thaut et al, 1997 ). Entrainment has also been demonstrated in infants ( Cantiani et al, 2022 ) and children ( LaGasse, 2013 ); however, there is evidence that perception action coordination may impact volitional movement accuracy ( Volman and Geuze, 2000 ). Although children have been shown to have the ability to entrain, children with developmental disabilities have demonstrated difficulties with rhythmic entrainment and/or timing ( Lense et al, 2021 ).…”
Section: Rhythmic Synchronization and Sensorimotor Facilitationmentioning
confidence: 99%
“…), researchers have shown the ability for individuals to spontaneously organize musical stimuli according to the meter and move to the stimulus ( Burger et al, 2018 ). Furthermore, neural entrainment to the metric organization of musical stimuli has been shown in adults ( Tierney and Kraus, 2015 ) and in children as young as 8 months ( Cantiani et al, 2022 ). Researchers have suggested that the neural response to meter-related frequencies occurs both at the subcortical and cortical level, with functional connections between the auditory cortex and motor structures ( Nozaradan et al, 2018 ).…”
Section: Rhythmic Synchronization and Sensorimotor Facilitationmentioning
confidence: 99%